2018
DOI: 10.1177/0961000618773133
|View full text |Cite
|
Sign up to set email alerts
|

Usability evaluation of a library website with different end user groups

Abstract: To ensure a certain degree of usability, a library website should be carefully designed, especially since end users constitute a multitude of people with different needs and demands. The focal objective of this research was to investigate how different types of end users (i.e. pupils, students, the working population, seniors and researchers) respond to a library website in terms of its effectiveness, efficiency and satisfaction, which together represent its usability. The answers were obtained by performing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
1
29
0
2
Order By: Relevance
“…A review of the related literature on usability of academic library websites showed that these studies had been generally carried out using methodologies other than cognitive walkthrough method [23][24][25][26] and this study was the first employing cognitive walkthrough method to meet the evaluation purposes.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the related literature on usability of academic library websites showed that these studies had been generally carried out using methodologies other than cognitive walkthrough method [23][24][25][26] and this study was the first employing cognitive walkthrough method to meet the evaluation purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Efficiency was measured by the time task [61,62,63,64], while the effectiveness was measured by successful task completion [61,62] using a three-point scale (where 1 means “Participant completed the task successfully”; 2 means “Participant completed the task successfully with the help of the moderator” and 3 means “Participant provided the wrong answer or gave up before completing the task”). Satisfaction was measured by the standardised questionnaire System Usability Scale (SUS) [61,62] developed by the Digital Equipment Corporation. Participants’ satisfaction was measured by a five-point Likert scale (where 1 indicated that the participants totally disagreed with the sentence, while 5 indicated that the participants totally agreed with it) and then evaluated with the SUS protocol [65].…”
Section: Empirical Researchmentioning
confidence: 99%
“…In accordance with the recommendations for usability testing procedure [62], the usability test was created and performed by an observational coding system called Morae. All three components of the system were used [62]: (1) Morae Recorder—used for the preparation and execution of usability testing; (2) Morae Observer—used for monitoring events on the participant’s screen and for the management of observational data; and (3) Morae Manager—used to manage data. Participants used the Morae Recorder for the entire time of the usability testing process, including questionnaires.…”
Section: Empirical Researchmentioning
confidence: 99%
“…The literature of libraries evaluation provides evidence that the majority of evaluation studies of digital libraries are related with usability (Kous et. al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Usability can be seen as a set of multiple constructs derived from various perspectives, such as effectiveness, efficiency, subjective pleasure, or memorability, with large focus on interface design (Jeng, 2006). Nielsen, who in the early 1990s, together with Rubin, developed usability engineering techniques for computer software design applied to Web design (Nielsen, 2003), establishes that usability "is a quality attribute that describes how easy user interfaces are to use" (Kous et. al., 2018).…”
Section: Introductionmentioning
confidence: 99%